What Makes Mathematics Teacher Coaching Effective? A Call for a Justice-Oriented Perspective. (November 2021) - Marshall, Samantha A.; Buenrostro, Patricia M.
Mathematics teacher coaching is a promising but largely overlooked form of professional development (PD) for supporting mathematics teachers' learning of justice-oriented teaching. In this article, we critically review the literature to illuminate what we currently know about mathematics teacher coaching and to highlight studies' contributions and limitations to inform future work. Broadly, we find that four programs of research have developed, investigating: (a) coaches' activities and relationships, (b) the effects of coaching on student assessment scores, (c) the effects of coaching on teachers' practices or behaviors, and (d) the effects of coaching on teachers' knowledge or beliefs. From this analysis, we argue that justice-oriented perspectives of teaching, in tandem with sociocultural theories of teachers' learning, could allow for more nuanced investigations of coaching and could support design of learning experiences for teachers that bring us closer to educational justice.